Mujahadatun nafs and riyadhatun nafs practices informing the religious personality among universities / Noraini Ismail ... [et al.] - Ismail, Noraini; Makhsin, Mardzelah; Mohd Zain, Zainab; Ismail, Ummi Syarah; Abdul Pisal, Nadhilah (2021)
Social problems involving university students have shown that some Muslim students still have a low level of religious personality. Based on the study, low level of religious personality will drag Muslim individuals to be involved with negative behaviour, while Muslim individuals with good religious personality will give birth to a Muslim community with noble morals and high level of religious appreciation. According to al-Ghazali, selfimprovement and the construction of religious personality can be done through the process of tazkiyah al-nafs (self-purification) by applying the concept of mujahadatun nafs (at-takhalli) and riyadhatun nafs (al-tahalli) in daily practice. This study aims to look at the impact of mujahadatun nafs (at-takhalli) and riyadhatun nafs (altahalli) practices on religious personality and the needs of these two concepts on forming religious personality among university students. Library research through content analysis method has been used in this study. Findings revealed that the concept of mujahadatun nafs (al-takhalli) and riyadhatun nafs (al-tahalli) can contribute to behavioural changes, shaping of morals and religious personality among Muslim. The implementation of these two concepts is needed as a solution and recovery to moral malfunctions and social problems involving students in university. The findings can be used as a guide for the university in developing human development programmes especially in the moral, spiritual aspect and strengthening religious personalities of the students